Potential role of Tamoxifen as a secondary analgesic for chemotherapy induced neuropathic pain - Thanaa A. El-Masry, Magda E. El Sayaad and Wafaa M. Fouda (Journal of Applied Pharmaceutical Science)
Pharmacological modulation of TRPV1 receptor is a promising way of producing analgesia in neuropathic pain models. in the present study we investigated the effect of Tamoxifen, PCK inhibitor ,on thermal hyperalgesia in rats after sciatic nerve injury induced by vincristine. Vincristine administration decreased the withdrawal latencies assessed by tail immersion and hot plate tests ,also it increased the level of inflammatory mediators , spinal NO and serum TNFα levels. Tamoxifen ,administered orally every 2 days one hour before vincristine injection till 7 times, resulted in the increase in withdrawal latencies compared to that of vincristine, also showed a decrease in spinal NO and serum TNFα levels. these findings suggested that TRPV1 receptor has a potential role in vincristine induced painful neuropathy and open the door for tamoxifen to be used as secondary analgesic in painful neuropathies.
Keywords: Tamoxifen, neuropathic pain, TRPV1, chemotherapy.